A genetic risk assessment for prostate cancer influences patients' risk perception and use of repeat PSA testing: a cross- sectional study in Danish general practice. Issue 2 (June 2020) - Fredsøe, Jacob; Sørensen, Karina Dalsgaard; Kirkegaard, Pia; Bro, Flemming; Edwards, Adrian; Vedsted, Peter
No abstract available